Improving Learning Outcomes of Basic Movements of Kicking a Ball Through Cooperative Learning in Class V Students of SD Negeri 4 Cot Girek - Zulkahiri (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to improve student outcomes through the implementation of Cooperative Learning in soccer lessons. Additionally, this research is conducted to gain in-depth information about the application of Basic Kicking Motion Learning using a cooperative approach. The research design is Classroom Action Research (CAR). The subjects in this study are 13 students from the fifth grade at SD N 4 Cot Girek. This research was conducted over two meetings consisting of two cycles. Each cycle consists of three sessions. The first cycle shows that through actions, students can enhance learning outcomes. From this first cycle, the result is that 23% of students have not yet achieved proficiency, indicating it is not yet complete. In the second cycle, as a reflection of the first cycle, it also shows that actions improve student learning outcomes. The result of the second cycle is 100% achieving proficiency, indicating completion. Based on the results of this research, it can be concluded that: (1) Cooperative Learning in soccer kicking material enhances student learning outcomes, (2) Basic Kicking Motion Learning using cooperative methods motivates students and makes them active participants in the learning process.